Department of Islamic Economics, Universitas Airlangga, Surabaya, Indonesia - Suyono, Joko; Eliyana, Anis; Rozzak, Muhammad Akbar (International Journal of Psychosocial Rehabilitation, 2020)
This study took the object of Zainuddin elementary school in the Sidoarjo Regency, Indonesia by raising the issue of affective commitment influenced by transformational leadership and mediated by inclusive organizational culture. The analytical method used in this study is SEM-PLS where the main function is to examine the influence of independent variables on the dependent variable and intervening variables on the dependent variable, namely the effect of transformational leadership on affective commitment mediated by inclusive organizational culture. Population and sample taken as many as 45 teachers, total teachers of the organization. The technique used is census, which is used to determine the number of respondents. The results of this study indicate that there is a direct influence of transformational leadership on affective commitment. The test results also showed the significance of inclusive organizational culture as a mediation between the effect of transformational leadership on affective commitment.